The Endothelium as a Target in Pediatric OSA - Kheirandish-Gozal, Leila (Frontiers in Neurology, 2012)
Pediatric sleep disordered breathing has emerged in the last few decades as a highly prevalent condition by virtue of its major morbidities encompassing the central nervous, cardiovascular, and metabolic systems. In this context, improved understanding of the pathophysiological mechanisms underlying the cellular and organ injury and repair mechanisms, and the variance of the phenotype at any level of disease severity is all the more critical if appropriate personalized therapies are to be developed in the future. In this paper, the current evidence and hypothetical framework pointing to the endothelium as a primary cellular target for many of the morbidities of pediatric sleep apnea is reviewed, and particular emphasis on the recruitment of the endothelial cell lineage will be explored. It is hoped that this perspective will foster both expansion and acceleration of discovery efforts aiming to ultimately prevent the potentially lifelong consequences of sleep apnea during childhood.